2021
DOI: 10.3390/economies9010023
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Education and Macroeconomic Variables on Corruption Index in G20 Member Countries

Abstract: The purpose of this study was to analyze the effect of several macroeconomic variables consisting of gross domestic products (GDP) per capita, economic openness, government effectiveness index, inflation, and the level of education on the corruption index in G20 member countries. This study focused on the effect of education on the level of corruption in the G20 member countries by treating other macroeconomic variables as control variables that were not analyzed in depth. This research used mixed methods with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 41 publications
0
4
0
2
Order By: Relevance
“…Our results support the evidence found in previous studies by Hauser (2019), Kao et al . (2022) and Maria et al . (2021) that confirm that learning and education significantly reduce corruption.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…Our results support the evidence found in previous studies by Hauser (2019), Kao et al . (2022) and Maria et al . (2021) that confirm that learning and education significantly reduce corruption.…”
Section: Resultsmentioning
confidence: 95%
“…In line with this, Sarwar and Hayat (2021) evidenced that education reduces violence and political instability improves the rule of law and economic growth. Maria et al (2021) showed that secondary education reduces corruption in G20 countries, developing countries and developed countries. In line with these studies, Dirwan (2019) concluded that preventive action against corruption through education is an important solution in Indonesia.…”
Section: Controlling Corruption Inmentioning
confidence: 99%
See 1 more Smart Citation
“…Nos aspectos relacionados à educação, Maria et al (2021) investigaram a relação da educação primária, secundária e terciária nos níveis de corrupção dos países do G20. Os resultados da pesquisa expuseram que a educação de nível secundário pode ser considerada como prioritária em grau de atenção e investimentos, reduzindo significativamente a corrupção em países desenvolvidos e em desenvolvimento.…”
Section: A Influência Dos Fatores Sociais Na Corrupçãounclassified
“…Em relação à variável Índice de Educação, assim como foi contatado na Hipótese 2, a educação contribui para com a transparência dos estados brasileiros e, consequentemente, para o combate da corrupção e redução dos seus índices. Esta afirmação se assemelha aos achados de Maria et al (2021), Ferraz, Finan & Moreira, (2012 e Asongu & Nwachukwu, (2015) ao afirmarem que a educação contribui para a redução das práticas da corrupção, uma vez que desenvolve uma mentalidade avessa aos conceitos da corrupção difundidos nos membros da sociedade, desde a fase infantil até a fase adulta. Ali & Isse (2003), Theobald (1990), Madanipour & Thompson (2020), Treisman (2000) e Tavares (2007), uma vez que consideram haver relação positiva entre a eficiência do sistema jurídico e a redução das práticas de corrupção, ou seja, um sistema jurídico eficiente na realização de seu propósito, coopera eficazmente no combate à corrupção na sociedade.…”
Section: Termos Da Equação Coeficientes Não Padronizados -Betaunclassified